PERANCANGAN DAN IMPLEMENTASI DATA WAREHOUSE UNTUK MENDUKUNG SISTEM AKADEMIK (STUDI KASUS PADA STKIP MUHAMMADIYAH KOTABUMI) - Khotimah, Khusnul; -, Sriyanto (244-5567)
Warehouse data is the place where the data can be saved in a wide scale. The capability ofÂ this warehouse in integrating data can ease academic division to serve the supporting informationÂ of the evaluation and taking decision analysis process. The problem is, in academic division, theÂ warehouse data has not provided yet to serve startegic report of taking decision process inÂ excecutive level. The aims of designing warehouse data which is made is to serve the strategicÂ information such as the total number of the new students per batch, studentsâ status, and theÂ number of outcomes based on the PGA and predicate. The method used in this research is KimballÂ method with nine-step methodology. The design of warehouse data which is built is excpected toÂ give an ease to academic division to manage histories data and provide startegic information toÂ support the evaluation and taking decision analysis in excecutive level.Keywords: warehouse data, academic dataÂ¸ STKIP muhammadiyah kotabumi